PENGARUH LATIHAN PLYOMATRICK TERHADAP PENINGKATAN KETERAMPILAN TENDANGAN SABIT PENCAK SILAT PADA PERGURUAN PENCAK SILAT PSHT SUKAKARYA - Muhammad Ade Pratama; Muhammad Supriyadi; Erick Salman ($$8@@&&$%K, 2021)
This study aims to determine how much influence plyometrick training has on the improvement of the skill of the pencak silat sickle kick in the martial arts college of loyal heart terate (PSHT) Sukakarya. This research is an experimental study using a pretest - posttest control group design with independent variables is plyometrick exercise. The dependent variable is the skill of the sickle kick and the sample is the brotherhood of loyal hearts terate in Sukakraya, Musi Rawas who were selected by sampling. To determine the experimental and control groups, the researcher used Purposive sampling technique with the ordinal pairing system. The data collection method used was a test. In each group, the test was given at the beginning before treatment and at the end after being given treatment. The treatment in the experimental group was in the form of plyometrick exercises. After being given treatment for 3 weeks with a frequency of exercise 6 times a week. Results: In the significance test of the difference with SPSS 16, it was found that Mean = 1.33 showed the difference between the pre testandposttest. the results of t-count = -9.6, df = 18 and p-value = 0.00 <0.05, which means that there is a significant difference between before and after the Plyometrick training treatment on the improvement of the skills of the pencak silat sickle kick in the pencak silat school of loyal heart terate (PSHT) ) Sukakarya.